A highly stable lithium metal anode enabled by Ag nanoparticle-embedded nitrogen-doped carbon macroporous fibers - Fang, Yongjin (2022)
Lithium metal has been considered as an ideal anode candidate for future high energy density lithium batteries. Herein, we develop a three-dimensional (3D) hybrid host consisting of Ag nanoparticle-embedded nitrogen-doped carbon macroporous fibers (denoted as Ag@CMFs) with selective nucleation and targeted deposition of Li. The 3D macroporous framework can inhibit the formation of dendritic Li by capturing metallic Li in the matrix as well as reducing local current density, the lithiophilic nitrogen-doped carbons act as homogeneous nucleation sites owing to the small nucleation barrier, and the Ag nanoparticles improve the Li nucleation and growth behavior with the reversible solid solution-based alloying reaction. As a result, the Ag@CMF composite enables a dendrite-free Li plating/stripping behavior with high Coulombic efficiency for more than 500 cycles. When this anode is coupled with a commercial LiFePO4 cathode, the assembled full cell manifests high rate capability and stable cycling life.